Program Pemberdayaan Masyarakat Melalui Digitalisasi BUMDes Dan Penguatan Literasi Digital Untuk Mendukung UMKM Dan Promosi Pariwisata - Putri Hayati; Agus Umar Hamdani (CV. Multi Kreasi Media, 2026)
This Community Service (PKM) activity was conducted in Sidowayah Village, Polanharjo District, Klaten Regency, with the aim of enhancing community capacity to utilize digital technology in support of Village-Owned Enterprise (BUMDes) services, MSME development, and the promotion of the village as a tourism destination. The challenges faced by the partners included suboptimal village information channels, low adoption of digital technology in MSME marketing, and limited promotion of the village's tourism potential. The implementation methods involved surveying and identifying partner needs, designing and developing a BUMDes website, conducting website usage outreach, providing digital marketing training for MSME operators, assisting with QRIS implementation, adding business locations to Google Maps, educating the community on social media and e-commerce usage, and documenting and publicizing the village's tourism potential. The results demonstrated that the BUMDes website successfully served as a village information and promotion platform manageable by the village government. MSME operators gained a better understanding of digital marketing, cashless payments, and the use of digital platforms to expand market reach. Furthermore, digital content-based tourism promotion activities helped increase Sidowayah Village's visibility as a tourism destination. Overall, the PKM activity had a positive impact by improving community digital literacy, strengthening the capacity of the BUMDes and MSMEs, and supporting sustainable, digitally-driven economic and tourism development in the village.